An Analysis of Gender Performativity in Iraj Mirza’s “Zohreh and Manouchehr” in the Light of Judith Butler’s Theories - Tarighat Bin, Maryam; Sadati, Seyyed Shahabeddin (LANGUAGE ART, 2023)
The present study investigated the gender roles in Iraj Mirza’s famous poem, “Zohreh and Manouchehr”, which is an adaptation of William Shakespeare’s Venus and Adonis. The theoretical framework of the study is Judith Butler’s theory of performativity. The researchers chose Iraj Mirza’s “Zohreh and Manouchehr” poem as the corpus of the study. To analyze the gender roles in this poem, the researchers first selected the lines which were pregnant with constructed male and female ideologies and then investigated the performativity theory in the lines. The current research is qualitative, which is considered a descriptive-analytical study. The findings revealed that gender roles between Zohreh and Manouchehr are not determined by their biological traits; male and female roles have been constantly changed, leading to sexual ambiguity. The analysis of the behaviors of these two characters showed that gender is not stable, and it is their performance that determines their genders, which is in line with Butler’s opinion. Additionally, the characters, particularly Zohreh, were not concerned with the norms of society; gender and sexuality were not explicit.